Step-by-step explanation:
g(x) = 3x - 2
g(-4) = 3(-4) - 2
= -12 -2
= -14
Answer:
x= -2y/3
-4y+4y=14
0y= 14
This has no solution.
Step-by-step explanation:
Answer In cases of two equations having two unknown variables the simultaneous method of solving the equations is adopted.
Supposing “0” as the value of “k” we will have the equation as 3x+2y=0
Then separating variable x will give, x= -2y/3
Substituting the value of x into the first equation that is: 6x + 4y = 14
6(-2y/3)+4y=14
Expanding this we get: 6(-2y/3)+4y=14
-4y+4y=14
0y= 14
Thus, no solution.
Answer:
Step-by-step explanation:
<u>Area of circle equation:</u>
Let the radius of bigger circle is x.
<u>We have:</u>
<u>Solve for x:</u>
- x² = 2(14²)
- x = √2(14²)
- x = 14√2 cm
The answer is F because you would have to multiply both 4 and 3 to get 12. Then you add both of the exponents for X to get 5. You wouldn't have to do anything for Y because you can't add it to anything.
Answer:
C
Step-by-step explanation: